El administrador educativo como líder académico - Miguel A. Gutiérrez-Rodríguez (Universidad Nacional, Costa Rica, 2001)
The author analyzes the dilemma facing educational administrators when they try to clarify their on beliefs and expectations regarding the role they are to perform. By and large, when these individuals become principals, they assume the role of administrators per se rather than that of academic leaders. This situation has serious implications for the improvement of the quality of education. To overcome this weakness, the author proposes the renewal of the academic offer of the universities with a new conceptual framework that holistically prepares the new generations of academic leaders.